Nature of Nation and State - Yuliana Yuli W; Satino Satino; Marina Ery Setiyawati (Journal Research of Social Science, Economics, and Management, 2021)
State defense is the attitude, action, and behavior of citizens, both individually and in groups, in maintaining the sovereignty and integrity of the country, which is based on a sense of love for the homeland, national and state awareness of the Unitary State of the Republic of Indonesia. This research is a qualitative descriptive study with a Focus and Group (FGD) approach. The Unitary State of the Republic of Indonesia based on Pancasila and the Law. The 1945 Constitution is willing to make sacrifices to ensure the survival of the Indonesian state from various threats, challenges, obstacles and disturbances (ATHG), both from within and from outside that endanger territorial integrity. Love for the homeland both together and with all components of the country in maintaining the existence of a safe, peaceful and controlled country.